THE USE OF CROSSWORD PUZZLE TO IMPROVE VOCABULARY MASTERY OF THE FIFTH GRADE STUDENTS OF SD N GOLO - Novia Lestari; Yuyun Yulia (Universitas Sarjanawiyata Tamansiswa, 2018)
The purpose of this research was to describe the procedures of using crossword puzzle to improve vocabulary mastery of the fifth grade students of SD N Golo.The design of this research was an action research. The research consisted of two cycles. The subject of the study was the fifth grade students of SD N Golo and the English teacher as the collaborator. The data collecting was done by observation, interview, and field notes. Hence, the data were in the form field notes and interview transcripts. The data analyzing used qualitative method in three steps: reducing the data, displaying the data, and drawing the conclusion. The result of the data showed that the use of crossword puzzle technique was able to improve the students’ vocabulary mastery. Based on the qualitative data, most of the students were active in learning activities and they could memorize the vocabulary. It could be seen from the students’ participation in responding the researcher’s instruction and the score of their task in the cycle 1 and cycle 2.